Trends in public agricultural spending in Swaziland - Nhlengethwa, Sibusiso B.; Matchaya, Greenwell C.; Musaba, Emmanuel; Chilonda, Pius (International Food Policy Research Institute, 2014)
Swaziland as a developing middle income country has continuously sought to create an enabling environment for the development of the agricultural sector. The country has enacted policies and strategies together with programs to facilitate the attainment of growth targets in the agricultural sector (World Bank, 2011). Consequently, this will lead to the attainment of the Comprehensive Africa Agriculture Development Program (CAADP) targets, Millennium Development Goals (MDGs) and facilitate economic growth.